Macys, Inc. : redrafting the brand architecture - Lamb, Amanda M.; Elston, Lauren P.; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
Macys controversial conversion of Chicago's State Street Marshall Fields store is just one of many branding and customer loyalty challenges facing Macys Inc. today. After converting over 800 stores nationwide, Macys focus is to remain relevant and competitive by managing customer perception of quality as well as reinvigorating the department store experience.
Originally published: Lamb, A. M., Elston, L. P., & ORourke, J. S. (2008). Macys, Inc.: Redrafting the brand architecture. 08-08. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Macy's, Inc. -- Public opinion; Department stores -- Illinois -- Chicago; Department stores -- Public relations -- Illinois -- Chicago; Branding (Marketing)